2005
DOI: 10.1557/mrs2005.208
|View full text |Cite
|
Sign up to set email alerts
|

Making Things by Self-Assembly

Abstract: Self-assembly-the spontaneous generation of order in systems of components-is ubiquitous in chemistry; in biology, it generates much of the functionality of the living cell. Self-assembly is relatively unused in microfabrication, although it offers opportunities to simplify processes, lower costs, develop new processes, use components too small to be manipulated robotically, integrate components made using incompatible technologies, and generate structures in three dimensions and on curved surfaces. The major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
130
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 46 publications
0
130
0
4
Order By: Relevance
“…The directed-or selfassembly of particles, also known as the ''bottom-up'' strategy, has great potential to overcome size limitations and processing restrictions of current ''top-down'' manufacturing processes, such as photolithography. [32][33][34][35] The anisotropic nature of the patchy particle surface enables a certain degree of control over the assembly process, since the specific interactions with and between patches can provide a driving force for assembly of a targeted structure. Several computational studies on the self-assembly of patchy particles have been reported and these have pushed the imagination of the patchy particle community to new heights.…”
Section: Introductionmentioning
confidence: 99%
“…The directed-or selfassembly of particles, also known as the ''bottom-up'' strategy, has great potential to overcome size limitations and processing restrictions of current ''top-down'' manufacturing processes, such as photolithography. [32][33][34][35] The anisotropic nature of the patchy particle surface enables a certain degree of control over the assembly process, since the specific interactions with and between patches can provide a driving force for assembly of a targeted structure. Several computational studies on the self-assembly of patchy particles have been reported and these have pushed the imagination of the patchy particle community to new heights.…”
Section: Introductionmentioning
confidence: 99%
“…2 Temperature/agitation. For self-assembly to occur, the assembling components need to interact via balancing repulsive and attractive forces, or they must be able to move and adjust their relative positions [64]. The thermal energy which moves around the components of the first stage (i.e.…”
mentioning
confidence: 99%
“…Self assembly promises a new paradigm for manufacturing small devices: instead of piece-by-piece manufacturing, structures could spontaneously assemble from individual components into functional devices [1,[3][4][5][6]. Enabling this technology requires understanding how to design parts, and protocols for their assembly, such that structures assemble with high yield.…”
mentioning
confidence: 99%